2003
DOI: 10.1108/00400910310495950
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to start‐up and their effect on aspirant entrepreneurs

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
2
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 20 publications
10
100
2
10
Order By: Relevance
“…A study of cognitive barriers by Pihkala and Vesalainen (2000) found that financial risk, social risk, lack of skills, and lack of commitment required to be an entrepreneur were major obstacles in the path. Robertson et al (2003) also found the fear of debt and failure, along with the difficulties in obtaining finance, to be significant obstacles in starting the business. On similar lines, Smith (1999) found that fear of business failure is one of the major hurdles to start a business and Iakovleva et al (2014) found cognitive barriers represented by lack of competence and lack of skills impeding business startup.…”
Section: Entrepreneurial Intention Among Studentsmentioning
confidence: 99%
“…A study of cognitive barriers by Pihkala and Vesalainen (2000) found that financial risk, social risk, lack of skills, and lack of commitment required to be an entrepreneur were major obstacles in the path. Robertson et al (2003) also found the fear of debt and failure, along with the difficulties in obtaining finance, to be significant obstacles in starting the business. On similar lines, Smith (1999) found that fear of business failure is one of the major hurdles to start a business and Iakovleva et al (2014) found cognitive barriers represented by lack of competence and lack of skills impeding business startup.…”
Section: Entrepreneurial Intention Among Studentsmentioning
confidence: 99%
“…Access to finance is also the most widely recognised object of entrepreneurship policy, and insufficient finance is regularly cited by non-entrepreneurs as a barrier to starting a business (Volery et al, 1997;Kouriloff, 2000;Robertson et al, 2003;Choo and Wong, 2006). There is some evidence that restricted competition in banking and government credit controls can restrict entry in the non-financial sector (Cetorelli and Strahan, 2006;Kawai and Urata, 2002).…”
Section: Financementioning
confidence: 99%
“…Most of the previous studies rely upon the trait theory. The trait theory focuses on personality traits, which drive an individual"s decision to become an entrepreneur (Robertson et al, 2003); or identifies common links or motivations among entrepreneurs that bind them together (Henderson and Robertson, 1999). As also noted by Day et al, (2006), this theory is concerned with what the entrepreneur does rather than what they are.…”
Section: Entrepreneurial Behaviour In Generalmentioning
confidence: 99%
“…However, research has suggested that various entrepreneurial characteristics are based on a number of theoretical perspectives. For detailed discussions of the perspectives of entrepreneurship see, Day, Reynolds, and Lancaster, 2006;Ratashobya, 1999;Robertson, Collins, Medeira and Slater, 2003. Most of the previous studies rely upon the trait theory.…”
Section: Entrepreneurial Behaviour In Generalmentioning
confidence: 99%